Petrographic and geochemical interpretations of source provenance and tectonic setting of the Lokoja Sandstone, Bida Basin, Nigeria - U. Ozulu, G.; U. Okoro, A.; O. Ndubueze, V. (International Journal of Advanced Geosciences, 2020)
The petrography and geochemistry of major and trace elements distribution pattern for the Lokoja Sandstones, Southern Bida Basin, Nigeria; were used to interpret their provenance, weathering conditions and paleotectonic setting. A total of seven (7) representative sandstone samples were selected for petrographic, heavy minerals and inorganic geochemical analyses; that is X- ray diffraction (XRD), X-ray fluorescence (XRF) and Laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS). Results of the petrographic analysis showed 52.14 % quartz, 39.29 % feldspar, 2.00 % rock fragments, 5.14 % matrix and cement fraction as well as 1.43 % unfilled voids. Results of major elements and oxides suggests intermediate to felsic source rocks while the dominance of Na-rich feldspar to the k-feldspar and high value of Fe2O3+MgO shows contribution from ferromagnesian minerals of mafic igneous source provenance and oceanic island arc region. Average concentrations of designated trace elements in the studied sandstones are low in concentrations. The lower concentrations of Cr, Co, and Ni and higher concentrations of Zr, Ba, and Sr suggest a felsic progenitor rock. But significantly high values of Ni (7.02 ppm), La/Co (7.99), and Ni/Co (3.28) as well as the low concentration value of Y, (3.23 ppm) suggests contributions from mafic source rocks. Low average ratios for La/Co, Th/Co, Th/Sc, Ni/Co, Cr/Ni, Cr/Sc, Cr/Th, Ni/Co, Cr/Ni, Cr/Th, Cr/Sc, Th/Sc, La/Co and Th/Co also suggest a felsic source provenance. An average CIA value of 78.04% is indicative of an intense recycling in the source area while an average MIA value of 56.13% suggests a moderate degree of weathering. The high clay matrix and feldspar content have been used to classify the sandstones as feldspathic greywackes deposited in dry arid climatic conditions under a basement uplifted tectonic setting.Â Â Â